TRAP Intrusion Arch-Modification of Transpalatal Arch for an effective Intrusion of Molars and Premolars - Shyagali, Tarulatha; Sen, Priyank; Tiwari, Rana (Journal of Orofacial Research, 2019)
The aim of the present clinic paper is to demonstrate an innovative design for the effective molar intrusion using TRAP appliance. Since its inception, Transpalatal Arch (TPA) has been modified to meet the various needs of orthodontic tooth movement and marathon of the modification continues still now. The applications of the transpalatal arch involve the three-dimensional control of the molar to active tooth movement of the molar as well. The design involves the usage of the properties of Niti open coil spring along with acrylic pad in TPA to bring about the effective molar intrusion.